Recent progress of fat reduction strategies for emulsion type meat products - Haozhen Zhang; Weiyi Zhang; Xianming Zeng; Xue Zhao; Xinglian Xu (Food Materials Research, 2022)
With the continuous improvement of living standards, people’s demand for meat products is increasing. However, the high fat content in traditional meat products will result in additional chronic diseases, causing harm to human health. Hence, there exists an urgent need for research on fat reduction technology of meat products. Recently, physical modification technologies and protein/carbohydrate/lipid/complex-based fat substitutes have gained great interest in reducing animal fat, which can simultaneously improve the technological and sensory properties of meat products. In this thriving field, many newly presented works lack comprehensive summary and critical comparison. Therefore, this paper reviews the latest research progress on the application of physical technologies and fat substitutes in fat-reduced meat products, highlighting their advantageous and disadvantageous in reducing total fat, improving the fatty acid profile and modifying technological and sensory properties of products. Finally, future trends are proposed with the aim to provide new insight into the development of quality fat-substituted meat products.